Development of a Transcultural Social Ethical and Integrated Care Model, for Dependent and Older People Populations at Risk of Exclusion in the Mediterranean Sea Basin (TEC-MED): A Research Protocol - Ana María Porcel-Gálvez; Elena Fernández-García; Soledad Vázquez-Santiago; Sergio Barrientos-Trigo; María Dolores Mateos-Garcia; Mercedes Bueno-Ferrán; Jalila El Ati; Hajer Aounallah-Skhiri; Marta Lima-Serrano (International Journal of Integrated Care)
Background: Higher life expectancy has produced a higher older people porpulation, not necessarily with a consistent quality of life, showing a high rate of vulnerability and dependence. The current social and health crisis situation has highlighted the need to create new integrated models of care that could be translated into social and health policies. Objective: The present study aims to develop, test, and validate an innovative integrated care model for older people with dependence and at risk of social exclusion and their caregivers. Methods: The TEC-MED project participants are nine project partners and six associated partners, with geographic coverage from six countries in the Mediterranean basin, Spain, Tunisia, Italy, Lebanon, Egypt, and Greece. Project coordination will take place at three different levels, macro, meso and micro, through six work packages. The pilot phase uses qualitative-quantitative method to assess the impact of the TEC-MED project, it is expected to train 36 Training Agents, six per country, who apply to a total of 28,200 people (mainly elders and their caregivers). Conclusion: The study proposes a new social integrated care organizational model focused on the integration of social and health care, comprising the governance model; the organization structure and the skills profiles for the caring personnel. Abstracta Antecedentes: La mayor esperanza de vida ha generado un incremento en la población de personas mayores, sin embargo, no necesariamente se ha traducido en una mejora constante de la calidad de vida, evidenciándose una alta tasa de vulnerabilidad y dependencia. La actual crisis social y sanitaria ha resaltado la necesidad de crear nuevos modelos integrados de atención que puedan traducirse en políticas sociales y de salud. Objetivo: El presente estudio tiene como objetivo desarrollar, probar y validar un modelo innovador de atención integrada para personas mayores con dependencia y/o en riesgo de exclusión social, así como para sus personas cuidadoras. Métodos: Los participantes del proyecto TEC-MED son nueve socios del proyecto y seis asociados, con cobertura geográfica en seis países de la cuenca del Mediterráneo: España, Túnez, Italia, Líbano, Egipto y Grecia. La coordinación del proyecto se llevará a cabo en tres niveles diferentes, macro, meso y micro, y a través de seis paquetes de trabajo. La fase piloto utiliza un método cualitativo-cuantitativo para evaluar el impacto del proyecto TEC-MED. Se espera capacitar a 36 Agentes de Formación, seis por país, quienes aplicarán el proyecto a un total de 28,200 personas (principalmente personas mayores y sus personas cuidadoras.). Conclusión: El estudio propone un nuevo modelo organizativo de atención social integrada, centrado en la integración de la atención social y sanitaria, que comprende el modelo de gobernanza, la estructura organizativa y los perfiles de competencias del personal de cuidado. Palabras Claves: Atención integrada; Dependencia; Personas mayores; Riesgo de exclusión; Transcultural